Generic data modeling based on the Markov chain theory part of an AutoML system: customizable library and visualization tool - Saldanha, Rodolfo Luis Dos Santos (2020)
Internship Report presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics